Association of Left Atrial Volume Index and In-hospital Outcome in Patients with Acute ST Segment Elevation Myocardial Infarction and It’s Correlation with the Level of NT-proBNP (Bangladesh Heart Journal, 2023)
Background: ST segment elevation myocardial infarction (STEMI) is associated with ventricular dysfunction due to ischemic myocardial damage, decrease ventricular compliance and increase filling pressure resulting in left atrial stretching, dilatation, increase left atrial volume and subsequently increase secretion of atrial natriuretic peptides. This study is aimed to determine the association between increase left atrial volume index (LAVI) and in-hospital outcome and to explore the correlation between LAVI and NT-proBNP in patients suffered from acute ST segment elevation myocardial infarction (STEMI).Methods: This cross sectional analytic study include 92 patients with acute STEMI admitted for reperfusion therapy. 2D Echocardiography was done and based on LAVI, study population were grouped as Group A:LAVI >34 ml/m2 (n=48) & Group B:LAVI d”34 ml/m2(n=44).Results: In-hospital outcome, plasma level of NT-proBNP and echcardiographic evaluation was done successfully. Mean NT-proBNP was significantly high in Group A than Group B (1234.6±738.77 vs 689.52±721.04). Statistically significant association was present between LAVI and adverse in-hospital outcome. Persistent chest pain, hypotension, acute LVF, arrhythmia, acute kidney injury were higher in Group A than Group B and acute LVF occurred significantly (p